Polymer Dielectrics Properties and Applications of - Du, Boxue (IntechOpen, 2017)
The book gives the reader an overview on electrical properties and applications such as converter transformer, transistor, and energy storage. Besides, this book also presents some recent researches on typical polymer material such as silicon rubber and LDPE, which may provide some clues of advanced polymer properties for both engineers and researches. The author has been a professor at the Department of Electrical Engineering, School of Electrical Engineering and Automation, Tianjin University, China, since 2002. He has been active in polymer insulation research since the 1990s. He is a member of IEEJ, senior member of CSEE, member at several WG in CIGRE, and associate editor of the IEEE Transactions on Dielectrics and Electrical Insulation.